2005
DOI: 10.1523/jneurosci.3107-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Polymodal Sensory Function of theCaenorhabditis elegansOCR-2 Channel Arises from Distinct Intrinsic Determinants within the Protein and Is Selectively Conserved in Mammalian TRPV Proteins

Abstract: Caenorhabditis elegans OCR-2 (OSM-9 and capsaicin receptor-related) is a TRPV (vanilloid subfamily of transient receptor potential channel) protein that regulates serotonin (5-HT) biosynthesis in chemosensory neurons and also mediates olfactory and osmotic sensation. Here, we identify the molecular basis for the polymodal function of OCR-2 in its native cellular environment. We show that OCR-2 function in 5-HT production and osmotic sensing is governed by its N-terminal region upstream of the ankyrin repeats d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 60 publications
(90 reference statements)
0
29
0
Order By: Relevance
“…The reasons for this discrepancy are not understood. Related to this study, it was recently reported that TRPV2 could rescue one particular deficit of the ocr-2 mutant, namely the dramatic downregulation of serotonin biosynthesis in the sensory ADF neuron, but mammalian TRPV2, unlike TRPV4 directing behavior in osm-9, did not complement the lack of the osmotic avoidance reaction of ocr-2 (Zhang et al 2004, Sokolchik et al 2005. However, common to these two investigations is the conservation of TRPV signaling across phyla that have separated for several hundred million years of molecular evolution, despite low sequence homology.…”
Section: Mammalian Trpv4 Directs Osmotic Avoidance Behavior In C Elementioning
confidence: 68%
“…The reasons for this discrepancy are not understood. Related to this study, it was recently reported that TRPV2 could rescue one particular deficit of the ocr-2 mutant, namely the dramatic downregulation of serotonin biosynthesis in the sensory ADF neuron, but mammalian TRPV2, unlike TRPV4 directing behavior in osm-9, did not complement the lack of the osmotic avoidance reaction of ocr-2 (Zhang et al 2004, Sokolchik et al 2005. However, common to these two investigations is the conservation of TRPV signaling across phyla that have separated for several hundred million years of molecular evolution, despite low sequence homology.…”
Section: Mammalian Trpv4 Directs Osmotic Avoidance Behavior In C Elementioning
confidence: 68%
“…37 Interestingly, replacing the TRPV ortholog in C. elegans, OCR-2, with human or mouse TRPV2 rescued the loss of chemosensory perception and showed a localization pattern along the sensory cilia and plasma membrane. 38 It is tempting to speculate that IGF-1 stimulation in ciliated mammalian cells may utilize TRPV2 at the cilium or plasma membrane to increase intracellular Ca 2+ levels and possibly result in ciliary resorption.…”
Section: Wnt Signalingmentioning
confidence: 99%
“…Many members of this superfamily are polymodally activated by a diverse assortment of environmental challenges, including osmotic, mechanical, and thermal stresses and cues [19,20]. For a variety of tissues, there is emerging evidence that regulatory volume responses are dependent on increases in Ca 2+ influx through pathways comprising several different members of the TRP superfamily [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%